Мобильные геофизические технологии: експерементальное изучение возможности применения для поисков скоплений углеводородов в районах распространения сланцев в Восточной Европе - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Божежа, Д.Н. (Геоінформатика, 2014)
Анализируются результаты экспериментального применения технологии частотно-резонансной обработки и декодирования данных дистанционного зондирования Земли (ДЗЗ) для обнаружения и картирования в зонах распространения сланцевых пород локальных участков скопления повышенных концентраций углеводородов (нефти, газа, газоконденсата). С использованием этой мобильной и оперативной технологии обработаны спутниковые снимки крупных поисковых участков и блоков на территориях распространения сланцевых комплексов в Украине, Польше, Румынии, Литве и Англии. В пределах обследованных участков обнаружены и закартированы аномальные зоны типа “залежь газа” (“залежь газа, нефти”). По параметрам (площади и максимальным значениям оценок пластового давления флюидов в коллекторах) многие аномальные зоны можно считать локальными участками для первоочередного детального изучения геофизическими методами и разбуривания. По сути это зоны “Sweet spots”. Начало освоения углеводородного потенциала на обследованных площадях с обнаруженных аномальных зон позволит существенно уменьшить экологическую нагрузку на окружающую среду. Установлено, что прогнозируемые продуктивные горизонты могут располагаться как выше, так и ниже сланцевых комплексов, поэтому при поисках скоплений углеводородов в районах распространения сланцевых пород целесообразно изучать практически весь (доступный для разбуривания) интервал разреза. Согласно результатам экспериментов, апробированная мобильная технология частотно-резонансной обработки и интерпретации данных ДЗЗ дает возможность оперативно обнаруживать и картировать зоны “Sweet spots” в пределах распространения сланцевых пород. Проаналізовано результати експериментального застосування технології частотно-резонансної обробки та декодування даних дистанційного зондування Землі (ДЗЗ) для виявлення та картування в зонах поширення сланцевих порід локальних ділянок скупчення підвищених концентрацій вуглеводнів (нафти, газу, газоконденсату). З використанням цієї мобільної та оперативної технології оброблено супутникові знімки великих пошукових ділянок і блоків на територіях поширення сланцевих комплексів в Україні, Польщі, Румунії, Литві та Англії. В межах обстежених ділянок виявлено та закартовано аномальні зони типу “поклад газу” (“поклад газу, нафти”). За параметрами багатьох аномальних зон (площею та максимальним значенням оцінок пластового тиску флюїдів у колекторах) можна вважати їх локальними ділянками для першочергового детального вивчення геофізичними методами та бурінням. По суті це зони “Sweet spots”. Початок освоєння вуглеводневого потенціалу на обстежених площах з виявлених аномальних зон дасть змогу істотно зменшити екологічне навантаження на навколишнє середовище. Встановлено, що прогнозовані продуктивні горизонти можуть розміщуватися як вище, так і нижче сланцевих комплексів, тому під час пошуків скупчень ВВ у межах поширення сланцевих порід доцільно вивчати практично увесь (доступний для буріння) інтервал розрізу. Відповідно до результатів експериментів, за допомогою апробованої мобільної технології частотно-резонансної обробки та інтерпретації даних ДЗЗ можна оперативно виявляти та картувати зони “Sweet spots” у межах поширення сланцевих порід. Purpose. Exploring the possibility of mobile and operational geophysical technologies using for the detection and mapping within the shale spreading areas of local areas with increased concentrations of hydrocarbon accumulations (oil, gas and gas condensate), within which the industrial (commercial) inflows of hydrocarbons can be obtained from boreholes. Experimental studies conducting within shale complexes spreading in Ukraine, Poland, Romania, Lithuania and England.
Design/methodology/approach. Experiments were carried out with the mobile technology of frequency-resonance processing and interpretation of remote sensing data using, which is the “direct” method of oil and gas exploration and operates within the “substantial” paradigm of geophysical investigations. The technologies and methods, developed on the principles of this paradigm, are aimed at the searching a particular (desired in each case) substance – oil, gas, condensate, gold, zinc, uranium, etc.
Findings. The anomalous zones of the “reservoir of gas” (“gas, oil”) type were detected and mapped within the surveyed license blocks. Parameters of many anomalous zones (areas and maximum estimates of fluid pressure in the reservoirs) allow us to classify them as promising objects, the probability of industrial (commercial) HC inflows from which is relatively high. The observed anomalies should be considered as priority local areas for detailed study by geophysical methods and drilling. This is essentially the “Sweet spots” zones. The received estimates of maximum values of reservoir pressure within the observed anomalous zones vary in a fairly wide range. This indicates that the projected productive horizons can be located both above and below the shale complexes. Therefore, the practically all (available for drilling) interval of the cross-section should be studied, when for the hydrocarbon accumulations prospecting within areas of shale spreading. Anomalous zones with very low values of fluid pressure in the reservoirs should not be considered as priority targets for detailed study.
Practical value/implications. The development of the surveyed license blocks starting from detected anomalous zones will allow, in general, significantly reduce the harmful effects (ecological pressure) on the environment. Mobile technology of frequency-resonance processing and interpretation (decoding) of remote sensing data allows to detect and map operatively the “Sweet spots” zones within the shale and other unconventional reservoirs spreading.